The Ketika Taruhan Menjadi Kebiasaan: Studi Faktor Pendorong Maraknya Judi Online di Kalangan Mahasiswa - Silalahi, Doli Sayuti Adhyaksa; Devan Algifhari; Muhammad Hafiz Eltarik (Lentera Jurnal Manajemen, 2025)
The phenomenon of online gambling is increasingly spreading among students in line with technological advancements and the high usage of digital media. Easy access, anonymity, and the widespread promotion on social media have made students one of the groups most vulnerable to exposure. Despite being illegal in Indonesia, this practice continues to grow through applications and websites that are difficult to curb. Students, as digital natives, often lack the information filters or awareness of the risks associated with online gambling, both academically, financially, and psychologically. This study aims to identify the factors that drive students to engage in online gambling and the impacts it causes. The method used is a descriptive qualitative approach through in-depth interviews with five active students from President University across various majors. The interviews were conducted semi-structured, lasting 5–10 minutes per respondent, and analyzed using thematic techniques to explore patterns of triggers, perceptions, and reflections on online gambling practices. The research findings revealed four main themes as drivers of involvement: curiosity and peer pressure, economic pressure, the need for escape from academic stress, and easy digital access. The impacts revealed included a decline in academic performance, disruption in social relationships, anxiety symptoms, and addiction. Although only two of the five respondents had directly participated, all showed a high level of exposure and concern regarding the widespread online gambling in the campus environment. This study recommends the need for contextual digital education, open counseling services, and collaboration between campuses and the government to limit access and enhance digital literacy among students.